The Role of Innovative Marketing in Improving the Mental Image of Insurance Companies' Clients in Lattakia (field study) (Journal of Hama University, 2021)
The research aimed to determine the role of the elements of the innovative marketing mix represented (product, pricing, distribution, promotion, material evidence, operations, individuals), in the mental image of insurance companies' clients in Lattakia Governorate, and to work on determining the level of the mental image formed in them, and the researcher relied on Descriptive approach, adopting a questionnaire that was distributed to 303 clients, and secondary data was collected, analyzed using appropriate statistical analysis methods, and results were extracted using SPSS, The research results that hat there is a moral relationship between the elements of innovative marketing and the mental image of customers, and the results of the analysis showed an acceptable degree of correlation, as the elements of innovative marketing contribute to a good degree in improving the mental image of the clients of the studied companies, and the overall average of customer evaluation was for the mental image variable of the companies under study. It was of a weak degree, as the clients did not have a desire to continue with the insurance companies that they deal with to a large extent and they feel confidence and credibility towards the company with which they deal with a moderate degree, and the research recommended the need to be aware of the importance of innovation in the elements of the marketing mix and the need to adopt it in the plans and policies followed, Given its great importance and role in improving the image of the public of customers, and working to urge the managers and employees of the studied companies to pay attention to the mental image and consider it as an important variable that has a role in enhancing the element of trust and credibility, and creating a positive impression on the public of customers in a way that contributes to improving the image and reputation of companies.